Manager redefined the competitive advantage in the middle of your organization - Davenport, Thomas O., 1952- (Jossey-Bass, 2010)
"In this book the author explains that managers must build human capital and engender employee engagement by managing them almost not at all, by attending instead to the factors and circumstances that make them successful. In other words, managers must play their role from offstage and out of the limelight. Based on a survey of over 16,000 employees, the author presents Towers-Perrins' management performance model: Executing tasks, Building relationships and performance capability, and Energizing change. Additionally, managers must create an atmosphere of authenticity and trust."--